Beyond Capacity: Exakte Phantasie and the Reconfiguration of Educational Normativity (Itinera, 2025)
This article argues for rethinking education in the Anthropocene as a site for reconfiguring subjectivity, rather than a reactive response to crisis. Framing the climate crisis as an aesthetic and phenomenological challenge, following Scott Hamilton and Dipesh Chakrabarty, it explores how ontological insecurity undermines the imagination of alternative futures. Drawing on Gayatri Chakravorty Spivak’s concept of planetarity, the article proposes an ethical and epistemological shift beyond universalizing frameworks, foregrounding alterity and contingency as central to educational thought. The argument develops through Theodor W. Adorno’s negative dialectics and his notion of education after Auschwitz, offering a model of negative normativity grounded in critical reflection on historical rupture and epistemic limits. Central to this is Adorno’s concept of exakte Phantasie, reimagined here as a pedagogical practice of receptive and speculative imagination. As a form of ars inveniendi, it fosters critical hope and imaginative agency within conditions of ecological and ontological uncertainty. Adorno’s critical and material reconceptualization of imagination, I argue, offers a new – performative – interpretation of aesthetic education, which is attuned to address contemporary socioeconomical and ecological challenges.